Biology and structure of arrestin proteins - Gurevich, Vsevolod V. (Henry Stewart Talks, 2021)
Arrestins, Arrestin-GPCR binding and signaling, Nanodiscs, Arrestin-rhodopsin binding, Arrestin protein biochemistry, Physiological effects of mutations